2021
DOI: 10.1002/bio.4062
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive and selective fluorescence sensing and imaging of Fe3+ based on a novel nitrogen‐doped graphene quantum dots

Abstract: A novel nitrogen-doped graphene quantum dots (N-GQDs) with a green fluorescence emission was synthesized through microwave method using citric acid and semicarbazide hydrochloride as reactants. The as-synthesized N-GQDs exhibited good stability, excellent water solubility, and negligible cytotoxicity. Due to intermolecular charge transfer, ferric ion (Fe 3+ ) has a strong quenching effect on the N-GQDs. Fluorescence quenching has a linear relationship with the Fe 3+ concentration in the range 0.02-12 μM. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…26,77 Most GQDs which detect Fe 3+ rely on a high affinity for nitrogen and oxygen surface groups in order to quench PL. 25,72,81,82 For example, it is hypothesised that phenolic groups on the surface of GQDs enhance Fe 3+ specificity, due to electron transfer between the excited state GQD and the d orbital of Fe 3+ , leading to PL quenching. 41,78,83 Many GQD sensors designed to detect Fe 3+ utilise precursors rich in oxygen-containing functional groups.…”
Section: Ferric Ion (Fe 3+ )mentioning
confidence: 99%
“…26,77 Most GQDs which detect Fe 3+ rely on a high affinity for nitrogen and oxygen surface groups in order to quench PL. 25,72,81,82 For example, it is hypothesised that phenolic groups on the surface of GQDs enhance Fe 3+ specificity, due to electron transfer between the excited state GQD and the d orbital of Fe 3+ , leading to PL quenching. 41,78,83 Many GQD sensors designed to detect Fe 3+ utilise precursors rich in oxygen-containing functional groups.…”
Section: Ferric Ion (Fe 3+ )mentioning
confidence: 99%
“…The static quenching process results from the formation of a non-fluorescent ground state complex (such as iron hydroxide), while the dynamic process is due to coordination between electron-rich NH 2 -and electron-deficient Fe 3+ . However, the majority of GQDs that detect Fe 3+ depend on high affinity for nitrogen and O-containing surface groups for quenching the fluorescence of GQDs [90,105,106]. Currently, sensors based on GQD utilize precursors that are rich in O-containing functional groups to form nitrogen and oxygen groups on the surfaces of QDs.…”
Section: Mercury Ionsmentioning
confidence: 99%
“…Currently, sensors based on GQD utilize precursors that are rich in O-containing functional groups to form nitrogen and oxygen groups on the surfaces of QDs. The surface groups can increase the number of functional groups on oxygen-containing surfaces and However, the majority of GQDs that detect Fe 3+ depend on high affinity for nitrogen and O-containing surface groups for quenching the fluorescence of GQDs [90,105,106]. Currently, sensors based on GQD utilize precursors that are rich in O-containing functional groups to form nitrogen and oxygen groups on the surfaces of QDs.…”
Section: Mercury Ionsmentioning
confidence: 99%
“…158 Recently, Wu et al reported a sensitive fluorescent sensing probe for Fe 3+ ion detection in HeLa cells and water samples with a LOD of 1.43 nM in the dynamic range of 0.02-12 mM. 187 Sahub et al used GQDs for the development of an optical pesticide sensor through the enzymatic reaction of choline oxidase (CHOx) and acetylcholinesterase (AchE) for the sensitive detection of organophosphate pesticide in water and food samples. 188 Mondal and their team prepared a N,S-GQD-based fluorescent sensing probe for TNP detection with a LOD of 19.05 ppb.…”
Section: Reviewmentioning
confidence: 99%
“…158 Recently, Wu et al reported a sensitive fluorescent sensing probe for Fe 3+ ion detection in HeLa cells and water samples with a LOD of 1.43 nM in the dynamic range of 0.02–12 μM. 187…”
Section: Biosensing Applications Of Gqdsmentioning
confidence: 99%